On the Discreteness of the Structural Space of Weakly Completely Continuous Banach Algebras - Mustafaev, G. S. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider a class of Banach algebras with irreducible finite-dimensional representations and prove that, for amenable Banach algebras from this class, the weak complete continuity implies the discreteness of their structural space.